Avaliação dos impactos do regime de precipitação atual no Sistema de Drenagem Urbana de Boa Vista - RR - Brands, Alexandre Gustavo (2023)
The episodes of flooding are constant in critical areas in the city of Boa Vista/RR, being mainly due to the flatness of the relief combined with the soil sealing caused by urban development, and such episodes cause financial, material and even human losses. In order to reduce this problem, this work proposed to present two equations that demonstrate the relationship Intensity-Duration-Frequency (IDF) of precipitation in the region, considering the rainfall records of a station maintained by INMET, one referring to the total period of data (1961-2022) and other considering the last 20 years of data. The Gumbel distribution of extremes and the daily rainfall disaggregation coefficients were applied to define the equation. The consideration of the partial period of records presented a more intense maximum rainfall regime, and this equation was used to verify the impacts on the urban drainage system of the city. The IDF equation generated was applied in a microdrainage project developed and executed by the Municipality of Boa Vista, where it was found that the intensities had an average increase of 10.26%, however, due to divergence in the application of conceptual design guidelines, the estimated flows had an increase of up to 1081% in certain stretches, changing considerably the expected sizing. The situation presented can be one of the factors that, associated with the lack of maintenance and periodic cleaning of the components, cause flooding in regions that are already equipped with urban drainage systems in the city.